2023
DOI: 10.3390/en16104195
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Properties and Fire Safety of Mineral Oil and Low-Viscosity Natural Ester Mixtures in Various Concentrations

Abstract: This paper presents the results of testing the electrical and fire properties of mineral oil and low-viscosity natural ester mixtures. Properties such as breakdown voltage, relative permeability, dispersion coefficient, conductivity, flash and burn point, and lower heating values were investigated in different concentrations of mixtures of the two liquids, as well as for the base liquids. To ensure equal humidity levels, the prepared samples of mixtures and base liquids were conditioned under identical climati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…This is due to their different structure and therefore other properties, for example, dielectric properties or the ability to exchange heat in a transformer. Below, we discuss issues related to fire protection [1], electrical [2], thermal [3], and gassing properties [4], the streaming electrification phenomenon [5], moisture [6,7], and the degradation of cellulose fibers [8] working with alternative liquids and their mixtures with mineral oil. Dombek and Gielniak, in [1], investigated the influence of the proportion of mixing mineral oil with natural ester with reduced viscosity on selected dielectric and fire properties.…”
Section: Alternative Liquidsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is due to their different structure and therefore other properties, for example, dielectric properties or the ability to exchange heat in a transformer. Below, we discuss issues related to fire protection [1], electrical [2], thermal [3], and gassing properties [4], the streaming electrification phenomenon [5], moisture [6,7], and the degradation of cellulose fibers [8] working with alternative liquids and their mixtures with mineral oil. Dombek and Gielniak, in [1], investigated the influence of the proportion of mixing mineral oil with natural ester with reduced viscosity on selected dielectric and fire properties.…”
Section: Alternative Liquidsmentioning
confidence: 99%
“…Below, we discuss issues related to fire protection [1], electrical [2], thermal [3], and gassing properties [4], the streaming electrification phenomenon [5], moisture [6,7], and the degradation of cellulose fibers [8] working with alternative liquids and their mixtures with mineral oil. Dombek and Gielniak, in [1], investigated the influence of the proportion of mixing mineral oil with natural ester with reduced viscosity on selected dielectric and fire properties. It was shown that mixing the two liquids can contribute to an increase in the flash point and burning of the resulting mixture, relative to the mineral oil.…”
Section: Alternative Liquidsmentioning
confidence: 99%
See 1 more Smart Citation